Captain Awesome gets crushed - Kirby, Stan; O'Connor, George (Little Simon New York, 2013)
Captain Awesome (otherwise known as Eugene McGillicudy) faces his latest challenge--making it through Valentine's Day at school while trying to find out the identity of his secret admirer